Nature and Scope of the Full Protection and Security Standard - niloofar saeedi; Pouria Askary (Faṣlnāmah-i Pizhūhish-i Huqūq-i Khuṣūṣī, 2021)
Full Protection and Security clause, as a standard for protecting foreign investors, is included in almost every Bilateral Investment Treaty. In comparison with other protection clauses specially Fair and Equitable Treatment, this standard is less discussed in arbitral awards and legal writings, however, it has a common feature with other protection standards which is vagueness and being subject of different interpretations and the fact that Bilateral Investment Treaties do not define Full Protection and Security either. As a result, arbitral tribunals feel free to interpret and determine the scope of the Full Protection and Security standard which can also result in divergence of opinions and different interpretations. Arbitral tribunals agree that this standard protects the physical integrity of investment but over time some Arbitral tribunals presented a wider interpretation of the concept and scope of Full Protection and Security making it also applicable to stability of legal and commercial environment and legal security of foreign investment. Arbitral tribunals’ different interpretations can be justified in light of their interpretation of the nature of host states obligations under Full Protection and Security clause.